Before Official Multiculturalism : Women's Pluralism in Toronto, 1950s-1970s. - Iacovetta, Franca (Toronto : University of Toronto Press, 2022)
Renowned author Franca Iacovetta provides a new perspective on multiculturalism by examining the hopes and challenges of women activists associated with the Toronto International Institute.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books